Impact of routine cell block preparation on results of head and neck fine needle aspirates. Issue 11 (4th September 2016) - Carter, Michael D.; Moore, David P.; MacIntosh, Rebecca F.; Bullock, Martin J.
Abstract : Background: Fine needle aspiration (FNA) of head and neck masses is a common technique for providing cytology specimens to guide patient management. Cell blocks made from these specimens can be beneficial. Policy at our institution was changed from production of cell blocks only when requested by the pathologist to routine production for all non‐parotid gland head and neck FNAs. The program was evaluated in terms of its impact on diagnosis and specimen turnaround time (TAT). Methods: A retrospective study was carried out using electronic records at our institution. The Intervention group consisted of FNAs obtained in the 15‐month period following implementation of routine cell block preparation ( n  = 391). The Control group consisted of the same specimens obtained in the 15 months prior to implementation ( n  = 403). The groups were compared with regards to diagnostic distribution into five categories—Unsatisfactory, Negative/Benign, Abnormal, Suggestive of Malignancy, and Malignant. Cytological‐histological correlation and TAT were also compared. Chi square and t tests with P  < 0.05 threshold were used. Results: There was no difference in diagnostic distribution between the two groups ( P  = 0.59) and TAT was unchanged ( P  = 0.74). Cytological‐histological correlation was borderline improved in the Intervention group, with fewer false negatives (33.0% Intervention, 44.3% Control, P  = 0.050). The cost of the program was estimated at CAD$53.60/cell block, or CAD$16, 771/year. Conclusion: Implementation of routine cell blocks for head and neck FNAs did not result in a difference in diagnostic distribution or improve case turnaround time despite incurring substantial cost. Correlation with final histology, however, was borderline improved, with fewer false negatives. Diagn. Cytopathol. 2016;44:880–887. © 2016 Wiley Periodicals, Inc.